Tissue and molecular features of aging in HIV infection - Abdul-Raoul Issa; Ibrehima Guindo; M Koulou; Nouhoum Sako; Djeneba Bocar Fofana; KL Nadjir; Sika Dossim; TY Nyasenu; Didier K Ekouevi; Anoumou Y Dagnra; Mireille Prince-David; mounerou Salou (Revue Malienne d’Infectiologie et de Microbiologie, 2017)
The widespread availability of antiretroviral therapy for all patients living with HIV (PLHIV) has radically transformed their health span and increased their life expectancy these last years. However, despite these optimistic data, some concerns about the impossible complete eradication of latent forms of the virus integrated into the host genome remain. Indeed, no treatment can cure HIV infection exists, and although immune system state is improving under treatment, it is never completely restored. While neither the effects related to the persistence of the virus or the side effects of treatments on long-term effect on the body is discussed, functional changes associated with premature aging are increasingly observed and described in HIVIP recent years. Thus, cardiovascular dysfunction, brain damage, immune hyperactivity or cancer considered as normal events in an elderly man it is also described in HIVIP. So this review is a detailed update on the condition of HIV infection accelerated aging.